Associations of Arterial Stiffness and Bone Mineral Density in Postmenopausal Women - O. Yu. Isaykina; I. A. Skripnikova; M. A. Kolchina; O. V. Kosmatova; V. E. Novikov; T. T. Tsoriev (Рациональная фармакотерапия в кардиологии, 2023)
Aim. To study associations  between arterial stiffness and bone mineral density in postmenopausal women.Material and methods. The intima-media thickness  (IMT), the presence  and  number  of atherosclerotic  plaques  (AP) were studied  using  duplex scanning. Pulse wave velocity (PWV), augmentation index (AI) were measured by applanation. The Bone mineral density (BMD) of the spine, hip neck (HN) and proximal hip (PH) was measured using double energy x-ray absorptiometry.Results. A significant  correlation  of PWV  with  age,  duration  of menopause was  revealed,  a more pronounced correlation  was  noted  with  blood pressure (BP), maximum IMT thickness.  There was no significant  correlation  between  PWV  and BMD.  AI showed  a statistically  significant but weak negative  correlation  with  the HN  (rs=0.12, p<0.05); a more  pronounced negative  correlation  was  obtained  for BMD  (rs=0.16, p<0.01). For indicators characterizing the degree of bone mass increased,  there is a significant  correlation with age (rs=-0.4, p<0.01), weight (rs=0.4, p<0.01), Quetelet index (rs=0.3, p<0.01) and the presence of AP (rs=-0.12, p<0.05). According to the results of multivariate regression  analysis,  the most significant  predictors of arterial stiffness were indicators  reflecting  obesity and diastolic BP. The relationship  between BMD and age-adjusted vascular stiffness was not statistically significant.Conclusion. In our study, postmenopausal women have increased arterial stiffness,  suggesting a higher risk of cardiovascular disease. The relationship between  bone mineral density and vascular  wall stiffness  was insignificant. To a greater extent,  arterial stiffness  depended  on age,  increased  blood pressure, and the presence of atherosclerotic  changes.